A Case Report on the Effectiveness of Plant Based Weight Loss Support Supplement for Weight Management - Pandya, Dr. Shridhar; Savaliya, Dr. Chetan; Lokhande, Dr. Megha; Nagore, Dr. Dheeraj (International Journal of Innovative Research in Medical Science, 2024)
Introduction: Obesity is a common health problem and it is increasing around the world. Herbal medicines are the mostly used alternative treatment for weight reduction. The aim of this study was to assess the efficacy of weight loss support for the treatment of obesity. Case Presentation: A total of 44 cases were analyzed over a 30-day treatment period. Participants received one tablet of the weight loss support product twice daily. The study assessed changes in body weight, inch loss, and constipation. Participants were provided with dietary counseling and encouraged to exercise daily. Co- morbidities, concomitant medications, and adverse events were monitored throughout the study period. Result and Discussion: The treatment resulted in significant weight reduction, with a mean 1.55 kg decrease after 15 days and a 2.84 kg decrease after 30 days (p<0.001). Notably, there was a 90% reduction in subjects experiencing constipation by day 30, indicating improved digestive health. Furthermore, 43.18% subjects experienced an inch loss >1 inch, while 56.81% had an inch loss of ≤1 inch. The product was well-tolerated, with no adverse events reported. Conclusion: This case study suggests that GPlife Healthcare's natural plant-based weight loss support product may be effective in supporting weight management. The herbal supplements should be used as part of a comprehensive weight management strategy that includes proper diet and exercise. Further research with larger sample sizes and longer durations is needed to confirm these findings and establish the long-term safety and efficacy of the product.